2021
DOI: 10.3389/fcell.2021.767888
|View full text |Cite
|
Sign up to set email alerts
|

Hematogenous Macrophages: A New Therapeutic Target for Spinal Cord Injury

Abstract: Spinal cord injury (SCI) is a devastating disease leading to loss of sensory and motor functions, whose pathological process includes mechanical primary injury and secondary injury. Macrophages play an important role in SCI pathology. According to its origin, it can be divided into resident microglia and peripheral monocyte-derived macrophages (hematogenous Mφ). And it can also be divided into M1-type macrophages and M2-type macrophages on the basis of its functional characteristics. Hematogenous macrophages m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 124 publications
(139 reference statements)
0
8
0
Order By: Relevance
“…M2-like macrophages exerted an anti-inflammatory effect and alleviated the pathology of renal injury [ 135 137 ], spinal cord injury [ 138 , 139 ] and sepsis-induced acute lung injury [ 140 ]; promoted angiogenesis [ 141 ] and stimulated the healing of pressure and diabetes wounds [ 142 , 143 ]. However, the outcomes of M2 treatment were not fully reproducible (reviewed in [ 144 ]), which, again, was attributed to the functional instability of in vitro polarized macrophages and their return to a neutral or even proinflammatory phenotype in in vivo surrounding [ 145 , 146 ].…”
Section: Developing Macrophage-based Cell Therapymentioning
confidence: 99%
“…M2-like macrophages exerted an anti-inflammatory effect and alleviated the pathology of renal injury [ 135 137 ], spinal cord injury [ 138 , 139 ] and sepsis-induced acute lung injury [ 140 ]; promoted angiogenesis [ 141 ] and stimulated the healing of pressure and diabetes wounds [ 142 , 143 ]. However, the outcomes of M2 treatment were not fully reproducible (reviewed in [ 144 ]), which, again, was attributed to the functional instability of in vitro polarized macrophages and their return to a neutral or even proinflammatory phenotype in in vivo surrounding [ 145 , 146 ].…”
Section: Developing Macrophage-based Cell Therapymentioning
confidence: 99%
“…The pro-inflammatory macrophage/microglia (M1 subsets) and anti-inflammatory macrophage/microglia (M2 subsets) are significant. Therefore, regulating the polarization of M1 and M2 macrophages/microglia can affect the inflammatory response process after SCI ( Buzoianu-Anguiano et al, 2021 ; Ding et al, 2021 ; Hashemizadeh et al, 2022 ). Previous studies have shown that acupuncture can ameliorate SCI by regulating M1 and M2 macrophages ( Zhao et al, 2017 ).…”
Section: Mechanism Of Acupuncture Therapy In Spinal Cord Injurymentioning
confidence: 99%
“…Based on their origin, macrophages can be divided into resident microglia and blood-derived macrophages. 25 Microglia originate from the embryonic yolk sac, tissue-retaining cells involved in central nervous system homeostasis. 45 After an SCI, neuroinflammation is mediated primarily by microglia.…”
Section: Spinal Cord Injury (Sci)mentioning
confidence: 99%
“… 1 Different macrophage roles in the acute and chronic phases of SCI making macrophages a new target for SCI therapy. 25 In the acute SCI phase, M1-type macrophages with stronger phagocytic and antigen-presenting abilities are the first to polarize. 26 In the chronic phase, M2 macrophages—which promote tissue repair—play a major role.…”
Section: Introductionmentioning
confidence: 99%